2021
DOI: 10.1111/aji.13471
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐linolenic acid regulates the gut microbiota and the inflammatory environment in a mouse model of endometriosis

Abstract: Problem This study aims to investigate the effects of alpha‐linolenic acid (ALA) on the gut microbiota (GM) and the abdominal environment in mice with endometriosis (EMS). Methods The effects of faecal microbiota transplantation (FMT) from EMS mice on mice treated with antibiotic cocktail were conducted. The 16S rRNA sequencing and PICRUSt software were used to detect the structure and function of GM respectively. The protein levels of Claudin 4 and ZO‐2 in the intestinal wall were detected using the western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…EM model mice were prepared according to a previously published study [ 16 ]. Every C57 mouse was injected with 0.2 mL of estradiol solution subcutaneously on the back of the neck three times at a frequency of one injection per 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…EM model mice were prepared according to a previously published study [ 16 ]. Every C57 mouse was injected with 0.2 mL of estradiol solution subcutaneously on the back of the neck three times at a frequency of one injection per 4 days.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that EMS changes the structure of the GM, causes an imbalance in the F/B ratio, and reduces the α and β diversity ( Ni et al, 1989a ; Ni et al, 1989b ), which are measures of the diversity of the microbiota within a single individual and an indicator to characterize the similarities in microbial composition between individuals, respectively ( Table 1 ). The imbalance in the GM leads to inflammation that damages the health of the intestinal epithelium and affects the health of the whole body through the downstream effects of metabolism.…”
Section: Relationship Between Ems and Gm Imbalancementioning
confidence: 99%
“…Studies have reported that IL-17A plays an important role in EMS progression ( Shi et al, 2022 ). Lactobacillus has long been used as a probiotic supplement to maintain health as well as prevent and treat diseases, but its proportion in GM elevated in EMS models ( Ni et al, 1989b ; Cao et al, 2020 ), which may be due to suppression of the differentiation of Th17 cells by Lactobacillus ( Wilck et al, 2017 ) . Furthermore, we found that the proportion of bifidobacteriaceae was elevated in some reports ( Ni et al, 1989b ; Yuan et al, 2018 ; Shan et al, 2021 ), and a high proportion of bifidobacteriaceae promoted the differentiation of Th17 cells ( Ang et al, 2020 ).…”
Section: Relationship Between Ems and Gm Imbalancementioning
confidence: 99%
See 2 more Smart Citations